The effect of anti-angiogenic agents on overall survival in metastatic oesophago-gastric cancer: A systematic review and meta-analysis. - David L Chan; Katrin M Sjoquist; David Goldstein; Timothy J Price; Andrew J Martin; Yung-Jue Bang; Yoon-Koo Kang; Nick Pavlakis (PLoS ONE)
Background Studies of anti-angiogenic agents (AAs), combined with chemotherapy (chemo) or as monotherapy in metastatic oesophago-gastric cancer (mOGC), have reported mixed outcomes. We undertook systematic review and meta-analysis to determine their overall benefits and harms. Methods Randomized controlled trials in mOGC were sought investigating the addition of AAs to standard therapy (best supportive care or chemo). The primary endpoint was overall survival (OS) with secondary endpoints progression-free survival (PFS), overall response rate (ORR) and toxicity. Estimates of treatment effect from individual trials were combined using standard techniques. Subgroup analyses were performed by line of therapy, region, age, performance status, histological type, number of metastatic sites, primary site, mechanism of action and HER2 status. Results Fifteen trials evaluating 3502 patients were included in quantitative analysis. The addition of AAs was associated with improved OS: HR 0·81 (95% CI 0·75-0·88, p<0·00001) and improved PFS: HR 0·68 (95% CI 0·63-0·74, p<0·00001). Subgroup analyses favoured greater benefit for OS in 2nd/3rd line settings (HR 0·74) compared to 1st-line settings (HR 0·91) (X2 = 6·00, p = 0·01). OS benefit was seen across all regions-Asia (HR 0·83) and rest of world (HR 0·75)-without significant subgroup interaction. Results from 8 trials evaluating 2602 patients were pooled for toxicity > = Grade 3: with OR 1·39 (95% CI 1·17-1·65). Conclusions The addition of AAs to standard therapy in mOGC improves OS. Improved efficacy was only observed in 2nd- or 3rd-line setting and not in 1st-line setting. Consistent OS benefit was present across all geographical regions. This benefit is at the expense of increased overall toxicity.